Չերքեզական ջոկատների մասնակցությունը 1915 թ. հայերի ցեղասպանությանը - Արսեն Ավագյան (ՀՀ ԳԱՍ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
В истории геноцида 1915 г. известны имена Черкеса Ахмеда и Халиля, организовавших депортацию и массовое уничтожение армян Артвина и Ванского вилайета, а также организовавшие убийство Григора Зограба и Вардкеса Серенгуляна. Большую роль в массовом уничтожении армян Эрзрумского вилайета сыграли черкесские отряды, известные под названием "Единение Ислама". In the history of Genocide of 1915 are famous the names of Circassians Ahmet and Halil, which organised the deportation and mass killings of Armenians from the vilayets of Artvin and Van, as well as the assassination of Grigor Zohrab and Vardkes Serengulyan. The main role in the mass killings of Armenians of the Erzurum vilayet was played by Circassian's bands known by the name "Unity of Islam".
Keywords: Պատմագրություն; Հայոց ցեղասպանություն (1915)